Isolation and nucleotide sequence of the GDP-mannose:cellobiosyl- diphosphopolyprenol α-mannosyltransferase gene from Acetobacter xylinum - Petroni, E.A. (1996)
A genetic locus from Acetobacter xylinum involved in acetan polysaccharide synthesis has been characterized. The chromosomal region was identified by screening a genomic library of A. xylinum in a Xanthomonas campestris mutant defective in xanthan polysaccharide synthesis. The A. xylinum cosmid clone can functionally complement a xanthan-negative mutant. The polymer produced by the recombinant strain was found to be indistinguishable from xanthan. Insertion mutagenesis and subcloning of the cosmid clone combined with complementation studies allowed the identification of a 2.3-kb fragment of A. xylinum chromosomal DNA. The nucleotide sequence of this fragment was analyzed and found to contain an open reading frame (aceA) of 1,182 bp encoding a protein of 43.2 kDa. Results from biochemical and genetic analyses strongly suggest that the aceA gene encodes the GDP- mannose:cellobiosyl-diphosphopolyprenol α-mannosyltransferase enzyme, which is responsible for the transfer of an α-mannosyl residue from GDP-Man to cellobiosyl-diphosphopolyprenol. A search for similarities with other known mannosyltransferases revealed that all bacterial α-mannosyltransferases have a short COOH-termina1 amino acid sequence in common.